DATA-DRIVEN ORGANIZATIONAL CHANGE MANAGEMENT: INNOVATION, LEADERSHIP, COMMUNICATION, AND TEAMWORK - MOMČILOVIĆ, Oliver; DOLJANICA, Dragan; BOURAIMA, Mouhamed Bayane; DOLJANICA, Suzana (Journal of process management and new technologies, 2026)
This paper examines the determinants of organizational change within the contemporary business environment, with a particular focus on innovation, leadership, business communication, and teamwork. The objective is to theoretically conceptualize and empirically determine the key factors that drive the dynamics and success of corporate transformational processes. The theoretical findings indicate that innovation serves as the primary vehicle for competitive advantage, leadership acts as the critical catalyst for change, business communication constitutes the foundational platform for information exchange, and teamwork facilitates the collective execution of strategic goals. The empirical results confirm the high predictive power of the model (R2=0.982), with the level of innovation exerting the most substantial impact (β=0.416), followed by leadership (β =0.217), business communication (β=0.206), and teamwork (β=0.152). The study concludes that organizational change emerges from a synergistic relationship among the analyzed determinants, with innovative processes playing a dominant role.